A meta-analysis of the prevalence, genotype distribution and risk factors for human papillomavirus infection in Nepal - Prayash Paudel; Asutosh Sah (PLoS ONE, 2025)
This systematic review and meta-analysis estimated the prevalence, genotype distribution, and risk factors for human papillomavirus infection among Nepalese women. A total of 8 cross-sectional studies with 6,082 participants were included in this review. For this review, the eligibility criteria included studies reporting HPV prevalence or genotype-specific rates among Nepalese women; thus, database sources were searched up to December 2024. The quality of the studies was assessed, and pooled estimates were computed via random effects models. The pooled prevalence of HPV infection among Nepalese women was 8.31%, with a genotype-specific prevalence of 2.62% for HPV-16 and 1.25% for HPV-18. HPV infection was significantly associated with those whose husbands had multiple sexual exposures. Other factors, including smoking status, educational status, and the use of contraceptives, were not significantly associated. Most analyses showed moderate to high heterogeneity. This review highlights the moderate burden of HPV infection in Nepal; hence, targeted public health intervention through vaccination and screening programs is recommended. Limitations include heterogeneity of studies and an inability to draw causal interference because all the data were cross-sectional. The findings highlight the need for region-specific strategies to combat HPV-related diseases in Nepal and underscore the importance of future research to address existing knowledge gaps. This review is registered in PROSPERO with registration number CRD42025632655.